Edukasi Keuangan untuk Remaja : Mempersiapkan Generasi Muda dalam Mengelola Keuangan pada Siswa Sekolah Tajaul Karomah Desa Situ Gadung Kabupaten Tangerang - Supriatna, Agus; Suhartono, Agus; Rahim, Eka (Jurnal PKM Manajemen Bisnis, 2025)
Financial literacy among youth is a crucial foundation for shaping a financially responsible generation. However, many teenagers lack adequate knowledge and skills in managing personal finances, which can lead to poor financial decisions in adulthood. In response to this issue, a Community Service Program (PKM) titled "Financial Education for Teenagers: Preparing the Young Generation to Manage Finances" was conducted at Tajaul Karomah School, Situ Gadung Village, Tangerang Regency. This program aimed to increase financial awareness and provide practical knowledge on financial management among high school students. The activity was held on April 12–13, 2025, involving 17 lecturers from Universitas Pamulang as facilitators. The participants included 25 students of Tajaul Karomah School, along with 15 attendees consisting of teachers and community members. The PKM activities employed interactive methods such as lectures, simulations, group discussions, and Q&A sessions to enhance engagement and understanding. As a result, the students showed significant improvement in their comprehension of financial concepts such as budgeting, saving, needs vs. wants, and the importance of early financial planning. Feedback from both students and teachers indicated that the activities were informative, engaging, and beneficial for real-life application. This program demonstrates the importance and effectiveness of early financial education in empowering youth to become more financially literate and responsible.